Genomic Analysis of Vascular Invasion in HCC Reveals Molecular Drivers and Predictive Biomarkers. Issue 6 (8th May 2021) - Krishnan, Maya S.; Rajan KD, Anand; Park, Jangho; Arjunan, Vinodhini; Garcia Marques, Fernando Jose; Bermudez, Abel; Girvan, Olivia A.; Hoang, Nam S.; Yin, Jun; Nguyen, Mindie H.; Kothary, Nishita; Pitteri, Sharon; et al.
Abstract : Background and Aims: Vascular invasion (VI) is a critical risk factor for HCC recurrence and poor survival. The molecular drivers of vascular invasion in HCC are open for investigation. Deciphering the molecular landscape of invasive HCC will help identify therapeutic targets and noninvasive biomarkers. Approach and Results: To this end, we undertook this study to evaluate the genomic, transcriptomic, and proteomic profile of tumors with VI using the multiplatform cancer genome atlas (The Cancer Genome Atlas; TCGA) data (n = 373). In the TCGA Liver Hepatocellular Carcinoma cohort, macrovascular invasion was present in 5% (n = 17) of tumors and microvascular invasion in 25% (n = 94) of tumors. Functional pathway analysis revealed that the MYC oncogene was a common upstream regulator of the mRNA, miRNA, and proteomic changes in VI. We performed comparative proteomic analyses of invasive human HCC and MYC‐driven murine HCC and identified fibronectin to be a proteomic biomarker of invasive HCC (mouse fibronectin 1 [Fn1], P  = 1.7 × 10 −11 ; human FN1, P  = 1.5 × 10 −4 ) conserved across the two species. Mechanistically, we show that FN1 promotes the migratory and invasive phenotype of HCC cancer cells. We demonstrate tissue overexpression of fibronectin in human HCC using a large independent cohort of human HCC tissue microarray (n = 153; P  < 0.001). Lastly, we showed that plasma fibronectin levels were significantly elevated in patients with HCC (n = 35; mean = 307.7 μg/mL; SEM = 35.9) when compared to cirrhosis (n = 10; mean = 41.8 μg/mL; SEM = 13.3; P  < 0.0001). Conclusions: Our study evaluates the molecular landscape of tumors with VI, identifying distinct transcriptional, epigenetic, and proteomic changes driven by the MYC oncogene. We show that MYC up‐regulates fibronectin expression, which promotes HCC invasiveness. In addition, we identify fibronectin to be a promising noninvasive proteomic biomarker of VI in HCC.